> 数学 >
计算.
(1)a+b+
2b2
a−b

(2)(x+1−
3
x−1
x+2
2x−2

(3)(2+
1
a−1
1
a+1
)÷(a−
a
1−a2
)
,其中a=2.
人气:270 ℃ 时间:2020-03-23 10:42:28
解答
(1)a+b+
2b2
a−b

=
(a+b)(a−b)
a−b
+
2b2
a−b

=
a2+b2
a−b

(2)(x+1−
3
x−1
x+2
2x−2

=[
(x+1)(x−1)
x−1
-
3
x−1
2(x−1)
x+2

=
(x+2)(x−2)
x−1
×
2(x−1)
x+2

=2x-4;
(3)(2+
1
a−1
1
a+1
)÷(a−
a
1−a2
)

=[
2(a+1)(a−1)
(a+1)(a−1)
+
(a+1)
(a−1)(a+1)
-
a−1
(a+1)(a−1)
]÷[
a(a+1)(a−1)
(a+1)(a−1)
+
a
(a+1)(a−1)
]
=
2a2
(a+1)(a−1)
×
(a+1)(a−1)
a3

=
2
a

把a=2代入原式得:原式=
2
a
=1.
推荐
猜你喜欢
© 2024 79432.Com All Rights Reserved.
电脑版|手机版